Factors affecting Web 2.0 adoption: a case study. Issue 1 (2014) - ,; ,
Abstract : Purpose – The main purpose of this paper is to identify factors affecting the adoption of Web 2.0 tools by librarians of academic libraries located in Hamedan, Iran.Design/methodology/approach – Methodologically, this survey is applied using a descriptive approach. The statistical population of the survey was 47 librarians of academic and college libraries located in Hamedan (Iran). The tool used for data gathering is a questionnaire made based on the relevant literature as well as authors' standpoint. It consists of 39 questions under ten broad factors. The collected data were analyzed with SPSS (version 16).Findings – Totally, ten broad factors affecting the adoption of Web 2.0 tools by the librarians were identified. The most effective factors are job conditions, changeability, skills, competitiveness, and saving time.Practical implications – To positively and effectively affect the adoption of Web 2.0 tools by librarians especially Hamedan academic librarians, holding training courses and related workshops, the inclusion of lessons regarding Web 2.0 tools and their application in the academic courses planned and run by LIS departments, implementing open and distance learning (ODL), attracting LIS professionals to the field of Web 2.0, buying needed software and hardware equipment, and addressing the importance of adopting and using Web 2.0 tools for academic and library managers should not be neglected.Originality/value – This study may contribute to the field in terms of better understanding of factors affecting the adoption of Web 2.0 tools and thus better usage of these and other emerging technologies in academic libraries and information centers. Acknowledgements : Special thanks to the participants whose help in doing the research is not forgettable. It is the authors' pleasure to extend their deep gratitude and thanks to the respected reviewers of the article for their helpful and constructive comments. They would heartily like to appreciate Dr Miguel‐Angel Sicilia who kindly gave them an opportunity to revise the present work and publish it through Program: electronic library and information systems .